2013
DOI: 10.1097/bsd.0b013e318246b163
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Cervical Arthroplasty Combined With Fusion Against 2-Level Fusion

Abstract: (1) The ROM of C56 (ProDisc-C arthroplasty) in HS was increased. (2) The HS model has a better ROM of C3-C7 than the TLF model. (3) The HS model offered less increase of adjacent segmental IDP and ROM than the TLF model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…In addition to ACDF and total ADR, the use of both methods has been reported. Outcomes after hybrid surgery are still under investigation, especially with regard to the effect on cervical kinematics at adjacent disc levels [ 24 ]. There is some suggestion that ADR located close to 2-level fusion may be a more challenging biomechanical environment compared to ADR alone [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ACDF and total ADR, the use of both methods has been reported. Outcomes after hybrid surgery are still under investigation, especially with regard to the effect on cervical kinematics at adjacent disc levels [ 24 ]. There is some suggestion that ADR located close to 2-level fusion may be a more challenging biomechanical environment compared to ADR alone [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific advent of finite element analysis has enabled the performance of dynamic studies and their applications in the automotive [26] and in the aircraft industries [27] , for military [28] and medical purposes [29] , for the investigation of the biomechanism in areas such as orthodontics [30] , [31] , implantology [32] , [33] , and blunt injuries [34] , and as a new tool to aid in the forensic sciences [35] . Research studies that utilize finite element analysis on ballistics issues to reproduce gunshot effects in the human skull remain sparse.…”
Section: Introductionmentioning
confidence: 99%
“…29 In terms of adjacent level ROM, heterogeneity exists in the biomechanical literature with most suggesting that HS decreases adjacent level ROM compared with 2-level fusion constructs. [30][31][32][33] Furthermore, the meta-analysis by Jia and colleagues observed that the intradiscal pressure was lower in the adjacent levels for HS than for 2-level fusions. Zhao et al 30 found that the intradiscal pressure increased by > 40% at adjacent levels in fusion models, whereas this was <10% in HS models.…”
Section: Two-level Constructs Biomechanical Studiesmentioning
confidence: 99%